2007
DOI: 10.1007/s11595-006-4760-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the cool system on internal stress of CaO-Al2O3-SiO2 glass-ceramic system

Abstract: The samples were attained through altering the cooling system of producing glass-ceramics. The X-ray diffraction was used to test the stress value of different samples. The relation of the cooling system and internal stress were also investigated. The experimental results show that the stress of glass-ceramic had a close relation with starting cool temperature. Above 800 ℃, glass-ceramic could be accelerated cooling and did not bring stress. Temperature between 500 ℃ and 800℃ was an important temperature range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…In terms of social effects, most studies have concluded that NRCFT enhances the stability of property rights in forestland [43][44][45] and reduced the occurrence of forest rights disputes [46][47][48]. NRCFT has also promoted the transfer of forest rights and given rise to forestry cooperative organizations [49][50][51], which stabilized the basic rural management system [52].…”
mentioning
confidence: 99%
“…In terms of social effects, most studies have concluded that NRCFT enhances the stability of property rights in forestland [43][44][45] and reduced the occurrence of forest rights disputes [46][47][48]. NRCFT has also promoted the transfer of forest rights and given rise to forestry cooperative organizations [49][50][51], which stabilized the basic rural management system [52].…”
mentioning
confidence: 99%